Penyuluhan Kekurangan Energi Kronis untuk Meningkatkan Pengetahuan Ibu Hamil dan Wanita Usia Subur - Yunri Merida; Shandy Wigya Mahanani (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2025)
Pregnancy is a crucial period requiring special attention, particularly regarding nutritional intake. Chronic Energy Deficiency (CED) in pregnant women is a condition where the mother experiences a prolonged lack of energy and protein intake, which can have detrimental effects on both maternal and fetal health. CED is often associated with poor nutritional status, characterized by a Mid-Upper Arm Circumference (MUAC) of < 23.5 cm. A deep understanding of CED during pregnancy is vital for improving the quality of maternal and child health and reducing mortality rates related to malnutrition. Klaten Regency, for instance, recorded a CED prevalence of approximately 15.8%. A study at Manisrenggo Community Health Center in Klaten identified that economic factors, a lack of nutritional awareness, and limited access to healthcare services contribute to the high incidence of CED. This community service activity aimed to enhance the knowledge of pregnant women and women of childbearing age regarding Chronic Energy Deficiency (CED) through educational intervention. A total of 35 participants took part in the counseling session, which covered the definition, impacts, prevention, and management of CED. The effectiveness of the counseling was measured by comparing participants' knowledge scores before and after the intervention using a paired samples t-test. The analysis results showed a significant average increase in knowledge scores of 1.647 points (p < 0.05). The calculated t-value of 11.200 (df=35) indicates a high strength of the counseling's influence. The counseling on Chronic Energy Deficiency (CED) conducted in Sotrunan Hamlet, Kecemen Village, Manisrenggo District, Klaten Regency, proved effective in increasing the knowledge of pregnant women and couples of childbearing age (PUS).   ABSTRAK Kehamilan merupakan periode penting yang memerlukan perhatian khusus, terutama dalam hal pemenuhan gizi. Kurang Energi Kronis (KEK) pada ibu hamil adalah kondisi di mana ibu mengalami kekurangan asupan energi dan protein dalam waktu lama, yang dapat berdampak buruk bagi kesehatan ibu dan janin. KEK sering dikaitkan dengan status gizi buruk, yang ditandai dengan Lingkar Lengan Atas (LILA) < 23,5 cm. Pemahaman mendalam tentang KEK pada kehamilan penting untuk meningkatkan kualitas kesehatan ibu dan anak serta menurunkan angka kematian terkait gizi buruk. Kabupaten Klaten, yang mencatat prevalensi KEK sekitar 15,8% . Studi di Puskesmas Manisrenggo, Klaten, mengidentifikasi bahwa faktor ekonomi, kurangnya kesadaran gizi, dan keterbatasan akses layanan kesehatan berkontribusi terhadap tingginya kasus KEK ini. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pengetahuan ibu hamil dan wanita usia subur mengenai Kekurangan Energi Kronis (KEK) melalui intervensi penyuluhan. Sebanyak 35 peserta berpartisipasi dalam kegiatan penyuluhan yang meliputi penjelasan mengenai definisi, dampak, pencegahan, dan penatalaksanaan KEK. Efektivitas penyuluhan diukur melalui perbandingan skor pengetahuan peserta sebelum dan sesudah intervensi menggunakan uji statistik paired samples t-test. Hasil analisis menunjukkan peningkatan skor pengetahuan rata-rata yang signifikan sebesar 1,647 poin (p < 0,05). Nilai t hitung sebesar 11,200 (df=35) mengindikasikan kekuatan pengaruh penyuluhan yang tinggi. Penyuluhan tentang Kurang Energi Kronik (KEK) yang dilaksanakan di Dusun Sotrunan, Desa Kecemen, Kecamatan Manisrenggo, Kabupaten Klaten terbukti efektif meningkatkan pengetahuan ibu hamil dan pasangan usia subur (PUS).